Synthesis of CeO2 -Pr2O3 Composites Applying for the Growth of Paramignya trimera - Hien, Tran Thi Thu; Ha, Nguyen Thi Thu; The, Do Minh; Hiep, Phan Phuoc Minh; Tam, Pham Thi Thanh; Ha, Dang Thi Ngoc; Chi, Nguyen Thi Kim; Thach, Pham Ngoc; Tung, Mai Hung Thanh; Chi, Nguyen Thi Phuong Le; Phuong, Tran Thi Thu; Quoc, Nguyen Tri (VNU Journal of Science: Natural Sciences and Technology, 2023)
In this paper, CeO 2 -Pr 2 O 3 composites were successfully fabricated using solid-phase heating and by varying the mass ratio of CeO 2 -Pr 2 O 3 (CP-11, CP-12, CP-13). These synthesized materials have been characterized by X-ray diffraction (XRD), Scanning electron microscope (SEM) and infrared spectroscopy (IR) and Energy-Dispersive X-ray spectroscopy (EDX). The obtained results showed that CeO 2 -Pr 2 O 3 materials affected the growth of Paramignya compared to the control sample. The growth of Paramignya trimera achieved the best result under investigation region when the mass of CeO 2 /Pr 2 O 3 is 1:2.